Parkin controls dopamine utilization in human midbrain dopaminergic neurons derived from induced pluripotent stem cells - Jiang, Houbo; Ren, Yong; Yuen, Eunice Y.; Zhong, Ping; Ghaedi, Mahboobe; Hu, Zhixing; Azabdaftari, Gissou; Nakaso, Kazuhiro; Yan, Zhen; Feng, Jian (Nature communications, 2012)
Parkinson's disease (PD) is defined by the degeneration of nigral dopaminergic (DA) neurons and can be caused by monogenic mutations of genes such as parkin. The lack of phenotype in parkin knockout mice suggests that human nigral DA neurons have unique vulnerabilities. Here we generate induced pluripotent stem cells from normal subjects and PD patients with parkin mutations. We demonstrate that loss of parkin in human midbrain DA neurons greatly increases the transcription of monoamine oxidases and oxidative stress, significantly reduces DA uptake and increases spontaneous DA release. Lentiviral expression of parkin, but not its PD-linked mutant, rescues these phenotypes. The results suggest that parkin controls dopamine utilization in human midbrain DA neurons by enhancing the precision of DA neurotransmission and suppressing dopamine oxidation. Thus, the study provides novel targets and a physiologically relevant screening platform for disease-modifying therapies of PD. Mutations in parkin, an ubiquitin ligase, cause an inherited form of Parkinson's disease. Here, Jiang et al . generate induced pluripotent stem cells from two patients with parkin mutations and find that neurons derived from the stem cells have defects in dopamine release, dopamine uptake and oxidative metabolism.